Penerapan Komunikasi Pembangunan Berkelanjutan dalam Pengelolaan Desa Wisata Berbasis Kearifan Lokal di Yogyakarta - Pupung Arifin; Nicolaus Nino Ardhiansyah (Universitas Merdeka Malang, 2020)
The researcher focuses on the concept of sustainable development communication as the existence of rural community collectivity which is still dominant. Collectivity and community self-help (gotong-royong) which become rural community characteristic becomes challenge and at the same time it is also an opportunity in managing tourism concept which is sustainable. The success of sustainable development is determined by the acceptance of each stakeholder on the changes being offered, and on how far they involve in deciding the changes they would like to make. The principles of communication in sustainable deveplopment has to guarantee the involvement and empowerment of local community, so that the local culture sustains to achieve the tourism which is environment friendly. This research found that main principal on sustainable development is the people. So various set of workshop and discussion held with Pinus Pengger Management to establishing mutual understanding among the management for taking ecological option. One of the example is about to replace branches for photo spots material into bamboo wood that available within the area. The management need to intensify the promotional aspect through social media to reduce plactic and paper material as promotional tools. Collectivism and gotong-royong culture that already exixted in those village, as one of social modality to ensure the best implementation on sustainabilty development principal in tourism village.Keywords: Tourism, Development Communication, Sustainable, Local WisdomDOI: https://doi.org/10.26905/nomosleca.v6i1.3958